Characterization of finishing with acid catalyst lacquer and nitrocellulose lacquer on sesenduk (endospermum diadenum) wood / Zilawati Kamal and Siti Zalifah Mahmud - Kamal, Zilawati; Mahmud, Siti Zalifah (2011)
The wood finishing process is the last treatment on artwork or a piece of wood to protect surface and to enhance the aesthetic value of the timber. In this study, sesenduk (Endospermum diadenum) was used to substitute the shortage of the commercial timber and as alternative material supply for furniture industry. The objective of this study was determined the performance of application acid catalyst lacquer (AC) and nitrocellulose lacquer (NC) as the finishing material for sesenduk wood Other then that, to investigate the performance of finishing system using acid catalyst lacquer (AC) and nitrocellulose lacquer (NC) as the finishing material for sesenduk wood Cross cut test, pull off test, impact test, abrasion test and resistance to household test were carried out accordance to ISO 2409;2007, ISO 4624;2002 and ASTM D4060-07 respectively. Based on the observation, the result show the AC and NC were easily to apply and give the good performance on sesenduk of wood surface. The performance of two by two systems (2 sealer + 2 lacquer) gave a good quality finishing on the product and are the best system as compare to one by one system (1 sealer + I lacquer). Beside that, both of that lacquer, AC and NC easy to apply with spraying technique. Generally the application of AC and NC were suitable to use as finishing material for sesenduk wood.